The role of nanotherapy in head and neck squamous cell carcinoma by targeting tumor microenvironment - Zhang, Ye; Dong, Pengbo; Yang, Lu (Frontiers in Immunology, 2023)
Head and neck squamous cell carcinomas (HNSCCs) refers to a group of highly malignant and pathogenically complex tumors. Traditional treatment methods include surgery, radiotherapy, and chemotherapy. However, with advancements in genetics, molecular medicine, and nanotherapy, more effective and safer treatments have been developed. Nanotherapy, in particular, has the potential to be an alternative therapeutic option for HNSCC patients, given its advantageous targeting capabilities, low toxicity and modifiability. Recent research has highlighted the important role of the tumor microenvironment (TME) in the development of HNSCC. The TME is composed of various cellular components, such as fibroblasts, vascular endothelial cells, and immune cells, as well as non-cellular agents such as cytokines, chemokines, growth factors, extracellular matrix (ECM), and extracellular vesicles (EVs). These components greatly influence the prognosis and therapeutic efficacy of HNSCC, making the TME a potential target for treatment using nanotherapy. By regulating angiogenesis, immune response, tumor metastasis and other factors, nanotherapy can potentially alleviate HNSCC symptoms. This review aims to summarize and discuss the application of nanotherapy that targets HNSCC's TME. We highlight the therapeutic value of nanotherapy for HNSCC patients.